2021
DOI: 10.1002/eom2.12144
|View full text |Cite
|
Sign up to set email alerts
|

Light‐responsive bilayered hydrogel for freshwater production from surface soil moisture

Abstract: The search and the utilization of alternative water resources to produce freshwater are highly important to the water shortage, especially in arid and desert regions. In these areas, the surface soil moisture (SSM) can be a promising water source, whereas its extraction and following release remain challenging. In this study, a light‐responsive bilayered hydrogel (LRBH) is designed to produce freshwater from SSM, which is obtained by the copolymerization of N‐isopropylacrylamide (NIPAM) and acrylic acid (AA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 75 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…Combined with the XPS results, it further indicated that PDA was attached to the hydrogel surface. Besides, we found that the N–H peak shifted from 1558 to 1546 cm –1 through the infrared spectra of PP 2 and PDA 2 @PP 2 –Cl, indicating the existence of hydrogen bonding between polydopamine and the hydrogel …”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Combined with the XPS results, it further indicated that PDA was attached to the hydrogel surface. Besides, we found that the N–H peak shifted from 1558 to 1546 cm –1 through the infrared spectra of PP 2 and PDA 2 @PP 2 –Cl, indicating the existence of hydrogen bonding between polydopamine and the hydrogel …”
Section: Resultsmentioning
confidence: 87%
“…Besides, we found that the N−H peak shifted from 1558 to 1546 cm −1 through the infrared spectra of PP 2 and PDA 2 @ PP 2 −Cl, indicating the existence of hydrogen bonding between polydopamine and the hydrogel. 28 3.4. Solar Thermal Conversion Efficiency.…”
Section: Chemical Structure Of Hydrogelmentioning
confidence: 99%
“…One approach to reducing the energy needed for sustainable water production is to use thermoresponsive hydrogels, specifically poly­( N -isopropylacrylamide) (PNIPAm), which exhibits an accessible lower critical solution temperature (LCST). Near the LCST at ∼33 °C, PNIPAm-based hydrogels can absorb and release liquid water via hydrophilic/hydrophobic switching. The low LCST for water releasea temperature readily achievable using natural sunlight as the heating sourcedistinguishes PNIPAm from other materials requiring high energy consumption. PNIPAm-based technologies have shown promise in wastewater purification, desalination, and moisture harvesting. Nevertheless, conventional PNIPAm (C-PNIPAm), characterized by a closed-pore structure, suffers from a slow response rate above the LCST due to the formation of a dense skin layer, which acts as a barrier that entraps absorbed water and reduces the water release rate . Thus, current solar-driven hydrogel-based water purification systems can produce only a few gallons of water per day, well below the recommended use of ∼15–40 gallons per person .…”
Section: Introductionmentioning
confidence: 99%
“…Hence through the development of intelligent materials, many alternatives can be proposed to respond to these priority needs. For example, PNIPAM‐based materials are developed for treatment, purification, recovery, desalination, 8–11 or; generating clean water 12…”
Section: Introductionmentioning
confidence: 99%